1994
DOI: 10.1016/0896-6273(94)90414-6
|View full text |Cite
|
Sign up to set email alerts
|

Localization of individual calcium channels at the release face of a presynaptic nerve terminal

Abstract: SummaryStudies using biophysical techniques suggest a highly structured organization of calcium channels at the presynaptic transmitter release face (LEnds et al., 1981; Stanley, 1993), but it has not as yet proved possible to localize identified channels at the required nanometer level of resolution. We have used atomic force microscopy on the calyx-type nerve terminal of the chick ciliary ganglion to localize single calcium channels tagged via biotinylated ~o-conotoxin GVIA to avidin-coated 30 nm gold partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 44 publications
6
84
0
Order By: Relevance
“…On the other hand, calcium channels were never found in patches of the exposed membrane surface of the bouton, in spite of the presence of a macroscopic calcium current (our unpublished observations). This could be explained by assuming that calcium channels are located in the releasing face of the bouton, as in other presynaptic terminals (Haydon et al, 1994). Should this be the case, it would reinforce the idea that type III boutons secrete into the synaptic space toward the muscle membrane.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, calcium channels were never found in patches of the exposed membrane surface of the bouton, in spite of the presence of a macroscopic calcium current (our unpublished observations). This could be explained by assuming that calcium channels are located in the releasing face of the bouton, as in other presynaptic terminals (Haydon et al, 1994). Should this be the case, it would reinforce the idea that type III boutons secrete into the synaptic space toward the muscle membrane.…”
Section: Discussionmentioning
confidence: 92%
“…The validity of such CgTx-based approaches (Jones et al, 1989;Robitaille et al, 1990;Cohen et al, 1991;Komura and Rakic, 1992;Filloux et al, 1994;Haydon et al, 1994;Mills et al, 1994) is substantiated by the similar temporal expression patterns of the 220 kDa ␣ 1B subunit, -CgTx binding sites, and overall Fl--CgTx labeling. Our study also agrees with that of Filloux et al (1994), who used [ 125 I] -CgTx autoradiography to explore N-VDCC ontogeny in the rat brain; however, we did not detect the developmental increase in [ 125 I] -CgTx affinity reported by these authors.…”
Section: Discussionmentioning
confidence: 92%
“…Expression studies indicate that the precise complexion of gene products in the ␣ 1 , ␣ 2 /␦, and ␤-VDCC heteromers defines their pharmacology and biophysical characteristics (Hofmann et al, 1994;Dunlap et al, 1995). However, specific VDCC subtypes also have unique patterns of expression in discrete brain regions and even within individual neurons (Jones et al, 1989;Robitaille et al, 1990;Westenbroek et al, 1990Westenbroek et al, , 1992Westenbroek et al, , 1995Cohen et al, 1991;Hell et al, 1993;Haydon et al, 1994;Mills et al, 1994;Elliott et al, 1995). Thus, neurons may exploit V DCC diversity to tailor voltage-dependent Ca 2ϩ influx in discrete f unctional compartments .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological studies have provided significant insights about the possible existence of presynaptic slots for VGCCs at transmitter release sites (Heuser et al, 1979;Robitaille et al, 1990;Haydon et al, 1994;Harlow et al, 2001). Biochemical studies have identified numerous molecular interactions between VGCCs and their binding partners that play a crucial role in coupling presynaptic VGCC to the release machinery (Sheng et al, 1998;Maximov et al, 1999;Missler et al, 2003;Spafford et al, 2003;Nishimune et al, 2004;Leenders et al, 2008).…”
Section: Introductionmentioning
confidence: 99%